Radar Derived Subglacial Properties and Landforms Beneath Rutford Ice Stream, West Antarctica. Issue 1 (7th January 2022) - Schlegel, Rebecca; Murray, Tavi; Smith, Andrew M.; Brisbourne, Alex M.; Booth, Adam D.; King, Edward C.; Clark, Roger A.
Abstract: Basal properties beneath ice streams and glaciers are known to be a control for ice flow dynamics, hence knowledge of them is crucial for predicting sea level due to changes in glacial dynamics. Basal properties, processes and topography also drive the formation of subglacial landforms. Bed properties beneath Rutford Ice Stream (West Antarctica) have previously been described using seismic acoustic impedance measurements at a sparse spatial coverage. Here, we derive bed properties in a 15 × 17 km grid of surface radar data with coverage and sampling much higher than previous seismic studies. Bed reflection amplitudes in surface radar data were calibrated using sediment porosities (ranging from 0.4–0.5) derived from seismic acoustic impedance. We find the bed properties are spatially variable, consisting of low porosity material in some areas and soft sediment in other areas. Comparison of seismic and surface radar data imply the low porosity material to be a consolidated sediment or sedimentary rock. Mega‐scale glacial lineations (MSGLs) are ubiquitous on the bed and consist of soft, high porosity, probably deforming sediment, consistent with previous interpretations of MSGLs. We find some MSGLs have high reflectivity on their crest, interpreted as water bodies overlying high porosity sediment, whereas the trough around and the upstream end of some landforms consist of low porosity material. Integrating these different observations, we place constraints on possible explanations for the occurrence of water on the crest of landforms. Plain Language Summary: Physical properties of rocks and sediments as well as the presence of water beneath ice streams and glaciers control the flow of the ice. Understanding glacial flow is important to better constrain predictions of sea‐level changes. Within this study we present physical properties of material beneath Rutford Ice Stream in West Antarctica over a 15 × 17 km area. Our data show areas of high porosity interpreted as wet sediment and areas of low porosity beneath the ∼2 km thick ice stream. Ice movement above areas of soft sediment is assumed to be maintained by sediment deformation, whereas in areas overlain by low porosity material, sliding of the ice over this material is assumed to maintain flow. The topography beneath Rutford Ice Stream shows many elongated landforms, some over 14 km long. We show that these landforms partly consist of soft sediment. Some of these seem to have a water layer on their crest, but it is not well understood why. However, there might be variations in the sediment composition of the landforms enabling the creation of this water layer. The occurrence of materials with different properties and water show us how heterogenous the bed beneath ice streams can be, which is important for modeling ice stream motion. Key Points: Glacier bed properties (water content, porosity) are constrained using surface radar data calibrated with seismic acoustic impedance Results show sequences of low porosity material (consolidated sediment or rock), soft sediment and free‐water beneath Rutford Ice Stream Mega‐scale glacial lineations are pervasive beneath ice streams, some with a free water layer >10 km long and 100 m wide along their crest